MASA DEPAN TEORI AKUNTANSI: TANTANGAN, INOVASI, DAN PELUANG - Hesti Wijayanti; Suciati; Arifa Ilmiyati; Gunawan Aji (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research discusses the future of accounting theory on the innovations, challenges, and opportunities that arise in the digital era. Recent technological developments, such as artificial intelligence, blockchain, and big data, have significantly changed the accounting landscape. This article has explored how these innovations can affect traditional accounting theories and open up new opportunities for more efficient and transparent accounting practices. On the other hand, it has also identified challenges, including ethical issues, data security, andregulatory changes. By analyzing the impact of technological developments, this research is able to provide insights into how the accounting profession can adapt and evolve in the future.